Comparison of the effectiveness of simple carbohydrates on hypoglycemic episodes in children and adolescents with type 1 diabetes mellitus: A randomized study in a diabetes camp. Issue 7 (9th August 2020) - Erbas, Ibrahim Mert; Abaci, Ayhan; Anik, Ahmet; Simsek, Erdem; Tuhan, Hale Unver; Kocyigit, Cemil; Yıldız, Melek; Dundar, Bumin Nuri; Bober, Ece; Catli, Gonul
Abstract: Background: Hypoglycemia is the most common and severe complication of insulin treatment during the management of type 1 diabetes mellitus (T1DM). Despite its importance, there is a lack of data about the efficacy and superiority of the carbohydrate sources used in hypoglycemia management in children and adolescents. Objective: We aimed to compare the effectiveness of honey, fruit juice, and sugar cubes as simple carbohydrates used in the primary treatment of hypoglycemia in children and adolescents with T1DM, who attended a diabetes summer camp. Methods: A prospective randomized study was performed in a 5‐days–long diabetes summer camp. Three different types of simple carbohydrates; sugar cubes, honey, or fruit juice were randomly given for the treatment of hypoglycemia and the recovery results in the three groups were compared. Results: About 32 patients (53.1% male, mean age 12.9 ± 1.9 years) were included and 158 mild hypoglycemic episodes were observed. Sugar cubes, honey, and fruit juice were given in 46 (29.1%), 60 (37.9%), and 52 (33%) events, respectively. We found that honey and fruit juice had similar efficiency in recovering hypoglycemia in 15 minutes with a rate of 95% and 98%, respectively. However, sugar cubes had a significantly lower impact on treatment of hypoglycemia than the others, with a recovery rate of 84.7% at 15 minutes. Conclusions: This study showed, for the first time, that honey and fruit juice were more effective in treating hypoglycemia than sugar cubes, and can be preferred in treating hypoglycemic events in children and adolescents with T1DM.